2015
DOI: 10.5696/i2156-9614-5-8.7
|View full text |Cite
|
Sign up to set email alerts
|

Mercury and Lead Contamination in Three Fish Species and Sediments from Lake Rukwa and Catchment Areas in Tanzania

Abstract: Lake Rukwa is one of the principal freshwater resources of Tanzania, meeting demands for drinking water, transport and fishery activities. Contamination of fresh water with heavy metals and pesticides is a matter of great concern in this region, as it is globally. Pollution of Lake Rukwa and rivers in the catchment area may have devastating effects to public water supplies and aquatic life, and lead to effects to human health. Pollution by heavy metals such as mercury (Hg), lead (Pb) and chromium (Cr), in part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…High levels of exposure to nonessential elements among local populations can occur in low‐ and middle‐income countries as a result of unregulated industrial practices and limited attention to waste management (Bose‐O’Reilly et al ; Nyanza et al ). In Tanzania, environmental monitoring studies in areas of artisanal and small‐scale gold mining have reported high arsenic (As) and mercury (Hg) concentrations in water, plant, and agricultural field soil samples, as well as from fish obtained from local rivers and ponds (Taylor et al ; Bose‐O’Reilly et al ; Nyanza et al ; Mshana ). Mercury is used in the amalgamation process to bind gold, whereas As is a constituent of most of the gold ore (Taylor et al ; Nyanza et al ).…”
Section: Introductionmentioning
confidence: 99%
“…High levels of exposure to nonessential elements among local populations can occur in low‐ and middle‐income countries as a result of unregulated industrial practices and limited attention to waste management (Bose‐O’Reilly et al ; Nyanza et al ). In Tanzania, environmental monitoring studies in areas of artisanal and small‐scale gold mining have reported high arsenic (As) and mercury (Hg) concentrations in water, plant, and agricultural field soil samples, as well as from fish obtained from local rivers and ponds (Taylor et al ; Bose‐O’Reilly et al ; Nyanza et al ; Mshana ). Mercury is used in the amalgamation process to bind gold, whereas As is a constituent of most of the gold ore (Taylor et al ; Nyanza et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 2: Health care delivery in Tanzania (Mshana, 2004) Statistics indicate there are 55 district hospitals, 13 designated district hospitals owned by Faith…”
Section: Existing Health Information Systems For Hospitals In Tanzaniamentioning
confidence: 99%